Hydrophobic elastomer as well as preparation method and application thereof
Elastomers with self-adhesion, self-healing and hydrophobic properties were prepared by mixing lauryl methacrylate and thiodecafluoctyl methacrylate in a specific proportion, and adding a photoinitiator and a crosslinking agent, an elastomer with self-adhesion, self-healing and hydrophobic properties were prepared by ultraviolet light irradiation. , solves the problem that it is difficult to achieve these performances simultaneously in the prior art, and realizes a high-performance elastomer suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411741157.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The prior art is difficult to achieve the self-adhesion, self-repair and hydrophobic properties of elastomers at the same time, and the preparation process is complex and energy-consuming.
Elastomers with self-adhesion, self-healing and hydrophobic properties were prepared by mixing lauryl methacrylate and thiodecafluoctyl methacrylate in a specific proportion, and adding a photoinitiator and a crosslinking agent, an elastomer with self-adhesion, self-healing and hydrophobic properties were prepared by ultraviolet light irradiation. .
It realizes the excellent mechanical properties, wide adhesion capabilities, significant self-repair performance and significant hydrophobic properties of the elastomer. It is suitable for a variety of application scenarios, including flexible electronics, medical patches and underwater sensors.
Smart Images

Figure BDA0005162631900000071 
Figure HDA0005162631910000011 
Figure HDA0005162631910000012
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new materials, and more specifically, to a hydrophobic elastomer and a preparation method and application thereof. Background Art
[0002] Elastomer is a kind of elastic polymer that can cause large deformation after being subjected to force, and can quickly recover to a state similar to the original size and shape after the external force dissipates. Due to the characteristics of high viscoelasticity, high elongation at break, and low Young's modulus, elastomeric materials are widely used in many fields such as construction, medical treatment, electronics, and automobiles. With the advent of the digital information age, research on high-performance portable flexible sensor devices has developed rapidly and is expected to be applied in the fields of human motion and health monitoring, intelligent robots, and wearable electronic devices. However, traditional metal and semiconductor sensors cannot meet the requirements of the field of flexible electronic devices due to their own high rigidity, small deformation, and poor human compatibility.
[0003] Elastomer materials are one of the important base materials for flexible strain sensors because of their high elasticity, high resilience and good skin compatibility. As flexible sensors, it is difficult to avoid damage caused by mechanical, chemical, thermal and ultraviolet radiation in practical applications, which leads to a decrease in their mechanical properties and a shortened service life. Therefore, giving the elastomer as a base material self-healing properties is of great significance to the service life of the device. As a base material for flexible sensors, it has self-adhesion ability, which is conducive to effective adhesion to surfaces such as skin, making it convenient to use. In addition, in order to avoid the influence of human sweat on flexible sensors, or to use flexible sensors underwater, the elastomer needs to have good hydrophobicity.
[0004] Chen Ruihu prepared an adhesive and hydrophobic elastomeric material. He used an emulsion polymerization method to prepare a three-component elastomeric material containing polyacrylate, metal nanoparticles and polydopamine (Chen Ruihu. Preparation of super-stretched polyacrylate elastomer and research on leather coating performance [D]. Qilu University of Technology, 2023.). The process is complicated and the dispersion stability and long-term performance of nanoparticles are limited. Wang Hui used polytetrahydrofuran, isophorone diisocyanate, diphenylmethane diisocyanate and 2-hydroxy-4-amino-6-methylpyrimidine to develop two polyurethane elastomers with adhesive and self-healing properties (Wang Hui. Molecular design and performance research of high-adhesion supramolecular elastomers [D]. Zhengzhou University, 2022.). The preparation process temperature is as high as 80°C, the preparation time exceeds 24 hours, the energy consumption is large and the raw materials are toxic.
[0005] Prior art CN115651118A proposes an underwater self-adhesive, self-repairing transparent ion conductive elastomer. It overcomes the defect that hydrophilic low eutectic solvents are easily affected by water molecules by designing a hydrophobic low eutectic solvent and combining soft and hard monomers. However, this scheme emphasizes ionic conductivity and optical transparency, but does not provide sufficient support for application scenarios that require hydrophobicity and high elasticity but do not require conductive properties (such as flexible non-conductive substrates, hydrophobic adhesive materials).
[0006] Prior art CN118047908A provides a hydrophobic ionic elastomer prepared from polyurethane acrylate and ionic liquid, which is mainly used for ionic conductivity and 3D printing rapid prototyping, but its mechanical properties (such as elongation at break and tensile strength) are limited and it is difficult to apply to scenes requiring high strength and high elasticity. Moreover, after the ionic liquid participates in the reaction, the material has poor flexibility and lacks self-healing ability.
[0007] According to current research reports, it is difficult for elastomers to have self-adhesion, self-healing and hydrophobic properties at the same time. Summary of the invention
[0008] The present invention provides a hydrophobic elastomer to overcome the defects of the elastomers described in the prior art that it is difficult to have self-adhesion, self-repair and hydrophobic properties at the same time, the preparation process is duplicable and consumes a lot of energy, etc.
[0009] Another object of the present invention is to provide a method for preparing a hydrophobic elastomer;
[0010] Another object of the present invention is to provide an application of a hydrophobic elastomer.
[0011] In order to solve the above technical problems, the technical solution of the present invention is as follows:
[0012] A hydrophobic elastomer is prepared from lauryl methacrylate, tridecafluorooctyl methacrylate, a photoinitiator and a crosslinking agent.
[0013] Furthermore, the molar ratio of lauryl methacrylate to tridecafluorooctyl methacrylate is 3-7:7-3.
[0014] The present invention innovatively proposes to mix lauryl methacrylate (providing a flexible segment) and tridecafluorooctyl methacrylate (providing hydrophobicity and rigidity) in proportion to achieve the mechanical properties and surface properties of the elastomer of the present invention. The fluorine group in tridecafluorooctyl methacrylate introduces low surface energy to give the material hydrophobicity. The dynamic intermolecular action of the elastomer enhances the self-healing ability of the elastomer of the present invention.
[0015] Furthermore, the photoinitiator is an oil-soluble photoinitiator; the content of the photoinitiator is 0.2% to 1.5% of the total amount of lauryl methacrylate and tridecafluorooctyl methacrylate.
[0016] Preferably, the photoinitiator is 1-hydroxycyclohexyl phenyl ketone and / or benzophenone.
[0017] Furthermore, the crosslinking agent is an acrylate crosslinking agent; the content of the crosslinking agent is 0.2% to 2% of the total amount of lauryl methacrylate and tridecafluorooctyl methacrylate.
[0018] Preferably, the crosslinking agent is 1,6-hexanediol diacrylate and / or ethylene glycol diacrylate.
[0019] Furthermore, the contact angle of water on the surface of the hydrophobic elastomer is greater than 100°.
[0020] Preferably, the contact angle of water on the surface of the hydrophobic elastomer can reach 110°.
[0021] Furthermore, the hydrophobic elastomer is sheared and self-repaired for 12 to 24 hours, and the tensile strain of the self-repaired hydrophobic elastomer is 500% to 920%.
[0022] Preferably, after the hydrophobic elastomer is sheared and self-repaired, the tensile strain of the self-repairing hydrophobic elastomer can be restored to at least 67% of the original value.
[0023] Preferably, after the hydrophobic elastomer is sheared and self-repaired, the tensile strain of the self-repairing hydrophobic elastomer can be restored to at least 123% of the original
[0024] A method for preparing the hydrophobic elastomer comprises the following steps: uniformly mixing lauryl methacrylate, tridecafluorooctyl methacrylate, a photoinitiator and a crosslinking agent; introducing an inert gas; and irradiating the hydrophobic elastomer with ultraviolet light to obtain the hydrophobic elastomer.
[0025] Furthermore, the inert gas is introduced for 10 to 30 minutes.
[0026] Preferably, the inert gas is nitrogen.
[0027] Inert gas is introduced to remove oxygen from the reaction system, preventing oxygen from consuming free radicals and ensuring polymerization efficiency. Nitrogen protection enhances the uniformity of free radical reactions and reduces side reactions, which is especially important under ultraviolet light.
[0028] Further, irradiate under ultraviolet light for 20 to 30 minutes.
[0029] UV curing is fast and efficient, avoiding the complexity of thermal curing process. The irradiation time directly affects the degree of cross-linking, thereby affecting the mechanical properties of the elastomer of the present invention.
[0030] Preferably, the wavelength of the ultraviolet light is 200-400 nm.
[0031] Preferably, the wavelength of the ultraviolet light is 365 nm.
[0032] An application of the hydrophobic elastomer, the hydrophobic elastomer has self-adhesion and can be applied to the adhesion of objects; the objects include metal, plastic, glass, and skin.
[0033] Preferably, it can be used for adhering objects in water.
[0034] An application of the hydrophobic elastomer is in the preparation of flexible electronics, medical patches, underwater sensors and waterproof materials.
[0035] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0036] 1. Excellent mechanical properties. Under different ratios, the mechanical properties of the elastomer show good adjustability, with tensile strength up to 740kPa and tensile strain greater than 1200%, showing high tensile strength and large tensile strain.
[0037] 2. Excellent and extensive adhesion. The elastomer of the present invention exhibits good adhesion to a variety of substrates (such as PET film, glass, copper sheet, pigskin, etc.). In the 90° peel strength test, the maximum peel strength for PET film is 100.00N / m, copper sheet is 30.74N / m, glass is 18.62N / m, plastic wrap is 19.80N / m, and pigskin is 11.48N / m. This shows that the elastomer of the present invention is suitable for a variety of application scenarios, especially for the combination of flexible plastic substrates, such as medical patches and flexible electronics.
[0038] 3. Excellent self-repairing performance. The tensile strain of the elastomer of the present invention recovers to 66.67% of the original value after 12 hours of self-recovery after shearing, and recovers to 122.67% of the original value after 24 hours of self-recovery. The self-repairing ability effectively extends the service life of the material and has important application value in the field of flexible electronics and structural materials that require long-term durability.
[0039] 4. Significant hydrophobicity. The elastomer of the present invention has low water absorption rate, and only a small amount of water is adsorbed on the surface after being soaked in water for 10 days. The water contact angle reaches 109.5°, indicating that the surface of the material has good hydrophobicity. The adhesion and mechanical properties of the elastomer of the present invention in the underwater environment are basically unaffected, and it is very suitable for scenes such as underwater sensors and waterproof coatings.
[0040] 5. The preparation process is simple and the mechanical properties are adjustable. It is quickly prepared through the UV-induced polymerization process without the need for complex equipment or high-temperature reactions. By adjusting the ratio of monomers and cross-linking agents, the material properties can be flexibly adjusted to meet different application requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 is a flow chart for the preparation of hydrophobic elastomer;
[0042] Figure 2 is a tensile stress-strain curve diagram of the elastomer obtained in Examples 1 to 5;
[0043] Figure 3 90° peeling curves of the elastomer adhered to various surfaces of materials obtained in Example 3;
[0044] Figure 4 The tensile stress-strain curve of the elastomer obtained in Example 3 before and after self-repair;
[0045] Figure 5 This is a graph showing the change in water absorption of the elastomer obtained in Example 4 when immersed in water over time;
[0046] Figure 6 This is a contact angle test photograph of the elastomer obtained in Example 5. DETAILED DESCRIPTION
[0047] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0048] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0049] Example 1
[0050] Operation process as Figure 1 As shown, lauryl methacrylate and methacrylate tridecafluorooctyl ester are added to the reaction container in a molar ratio of 3:7; then a photoinitiator 1-hydroxycyclohexyl phenyl ketone is added in an amount of 0.2% of the total molar amount of lauryl methacrylate and methacrylate tridecafluorooctyl ester; then a crosslinker 1,6-hexanediol diacrylate is added in an amount of 0.2% of the total molar amount of lauryl methacrylate and methacrylate tridecafluorooctyl ester. After stirring and mixing evenly, nitrogen is introduced into the mixed solution for 10 minutes, and the mixed solution is transferred to a silicone mold and irradiated under a 365nm wavelength ultraviolet lamp for 30 minutes to obtain an elastomer with self-adhesion, self-repairing and hydrophobic properties.
[0051] Example 2
[0052] Operation process as Figure 1 As shown, lauryl methacrylate and methacrylate tridecafluorooctyl ester are added to the reaction container in a molar ratio of 4:6; then a photoinitiator 1-hydroxycyclohexyl phenyl ketone is added in an amount of 0.5% of the total molar amount of lauryl methacrylate and methacrylate tridecafluorooctyl ester; then a crosslinker 1,6-hexanediol diacrylate is added in an amount of 0.5% of the total molar amount of lauryl methacrylate and methacrylate tridecafluorooctyl ester. After stirring and mixing evenly, nitrogen is introduced into the mixed solution for 20 minutes, and the mixed solution is transferred to a silicone mold and irradiated under a 365nm wavelength ultraviolet lamp for 20 minutes to obtain an elastomer with self-adhesion, self-repairing and hydrophobic properties.
[0053] Example 3
[0054] Operation process as Figure 1 As shown, lauryl methacrylate and tridecafluorooctyl methacrylate are added to the reaction container in a molar ratio of 5:5; then a photoinitiator 1-hydroxycyclohexyl phenyl ketone is added in an amount of 1.0% of the total molar amount of lauryl methacrylate and tridecafluorooctyl methacrylate; then a crosslinker 1,6-hexanediol diacrylate is added in an amount of 1.0% of the total molar amount of lauryl methacrylate and tridecafluorooctyl methacrylate. After stirring and mixing evenly, nitrogen is introduced into the mixed solution for 20 minutes, and the mixed solution is transferred to a silicone mold and irradiated under a 365nm wavelength ultraviolet lamp for 25 minutes to obtain an elastomer with self-adhesion, self-repairing and hydrophobic properties.
[0055] Example 4
[0056] Operation process as Figure 1 As shown, lauryl methacrylate and tridecafluorooctyl methacrylate are added to the reaction container in a molar ratio of 6:4; then a photoinitiator benzophenone is added in an amount of 1.5% of the total molar amount of lauryl methacrylate and tridecafluorooctyl methacrylate; then a crosslinking agent ethylene glycol diacrylate is added in an amount of 1.0% of the total molar amount of lauryl methacrylate and tridecafluorooctyl methacrylate. After stirring and mixing evenly, nitrogen is introduced into the mixed solution for 30 minutes, and the mixed solution is transferred to a silicone mold and irradiated under a 365nm wavelength ultraviolet lamp for 20 minutes to obtain an elastomer with self-adhesion, self-repairing and hydrophobic properties.
[0057] Example 5
[0058] Operation process as Figure 1As shown, lauryl methacrylate and tridecafluorooctyl methacrylate are added to the reaction container in a molar ratio of 7:3; then a photoinitiator benzophenone is added in an amount of 0.5% of the total molar amount of lauryl methacrylate and tridecafluorooctyl methacrylate; then a crosslinking agent ethylene glycol diacrylate is added in an amount of 2.0% of the total molar amount of lauryl methacrylate and tridecafluorooctyl methacrylate. After stirring and mixing evenly, nitrogen is introduced into the mixed solution for 20 minutes, and the mixed solution is transferred to a silicone mold and irradiated under a 365nm wavelength ultraviolet lamp for 25 minutes to obtain an elastomer with self-adhesion, self-repairing and hydrophobic properties.
[0059] Comparative Examples 1 to 4
[0060] The technical solutions of Comparative Examples 1 to 4 are similar to Example 1, except that the molar ratios of lauryl methacrylate and tridecafluorooctyl methacrylate are 1:9, 2:8, 9:1 and 8:2, respectively.
[0061] Test Method
[0062] 1. Tensile strength
[0063] The dumbbell-shaped sample (5 mm wide and 1 mm thick) was tested for stress-strain curve by a universal mechanical testing machine at a strain rate of 50.00 mm / min.
[0064] 2. 90° adhesion peel strength
[0065] The adhesion of the sample (25 mm in length, 5 mm in width, and 1 mm in thickness) on the surface was tested using a universal mechanical testing machine and a 90° adhesion peeling fixture at a peeling rate of 50.00 mm / min.
[0066] 3. Self-repair
[0067] Cut a piece of elastomer sample with a length of 3 cm and a width of 5 mm, cut it in the middle, then put the two small pieces of sample in close contact at the fracture, wrap them with plastic wrap, and place them at room temperature for self-healing for 12 hours, and then perform stress-strain test after 12 hours.
[0068] 4. Water absorption
[0069] The sample was placed in pure water and soaked for 10 days, and the mass of the sample was measured every day. The swelling rate versus time line graph was calculated according to the following formula.
[0070]
[0071] Where R is the swelling ratio, Mn (g) is the sample mass recorded each day, and M0 (g) is the initial mass of the sample.
[0072] 5. Contact angle
[0073] Use a contact angle tester to test the contact angle of a water drop on the elastomer surface.
[0074] Results Analysis
[0075] The tensile properties of the elastomer come from the three-dimensional cross-linked network. Lauryl methacrylate provides flexible segments, and tridecafluorooctyl methacrylate provides hydrophobicity and rigidity. The flexible segments give the material high ductility, and the cross-linked structure improves the tensile strength. Figure 2 As shown, at different ratios of lauryl methacrylate to tridecafluorooctyl methacrylate, the tensile strength and strain vary significantly, showing the adjustability of the mechanical properties of the resulting elastomer. In Example 1, a tensile strength of 740 kPa and a tensile strain greater than 1200% were achieved, showing good toughness and balanced performance, suitable for applications requiring high strength and high elasticity. The tensile strengths of the hydrophobic elastomers obtained in Examples 2 to 5 were 480 kPa, 360 kPa, 140 kPa, and 50 kPa, respectively.
[0076] The adhesion of the elastomer comes from the flexibility of the molecular chain and the dynamic interaction between molecules. The flexible chain segment can closely adhere to the surface of different substrates, and the hydrophobic group and van der Waals force provide strong adhesion. The elastomer prepared by the present invention can adhere to the surface of PET film, copper sheet, pig skin, glass, cling film, etc., and the 90° adhesion peel strength is as high as 100%. Figure 3 As shown, the maximum peeling strength of the elastomer of Example 3 to PET film can reach 100.00N / m, the maximum peeling strength to plastic wrap can reach 19.80N / m, the maximum peeling strength to glass can reach 18.62N / m, the maximum peeling strength to copper sheet can reach 30.74N / m, and the maximum peeling strength to pig skin can reach 11.48N / m. The results show that the elastomer of the present invention has excellent self-adhesion ability on a variety of substrates, and exhibits the highest adhesion strength on PET film, indicating that the material is suitable for combination with flexible plastic substrates, especially in flexible electronics, medical patches and other scenes requiring adhesion performance.
[0077] The self-repairing function of the elastomer of the present invention relies on the dynamic interaction between molecules. The hydrophobic interaction and van der Waals force promote the rearrangement and bonding of molecules at the fracture interface. The low surface energy characteristics of the fluorine group reduce the friction resistance of the repair interface. Figure 4 As shown, the original tensile strain of the elastomer in Example 3 is 750%. After being sheared and allowed to self-repair for 12 hours, the tensile strain is 500%. After 24 hours of self-repair, the tensile strain of the elastomer is 920%, indicating that the elastomer of the present invention has excellent self-repair performance, and extending the self-repair time can significantly improve the mechanical properties, and the tensile strain after repair can exceed the original value.
[0078] The fluorine group in methacrylate tridecafluorooctyl has low surface energy characteristics, and the surface structure formed hinders the penetration of water molecules. Example 4 After the elastomer is immersed in water for 10 days, the water absorption rate is very low ( Figure 5 ), only a small amount of water is adsorbed on the surface, and the contact angle of the water droplet on the surface of the elastomer of Example 5 is 109.5° ( Figure 6 ), the low water absorption rate of the elastomer of the present invention reflects its significant hydrophobicity. When used in an underwater environment, the material properties will not be significantly affected by water absorption, and it is very suitable for applications such as underwater sensors.
[0079] In the comparative example, when the molar ratio of lauryl methacrylate and 13-fluorooctyl methacrylate is 1:9 or 2:8, the proportion of rigid monomer (13-fluorooctyl methacrylate) is too high, and the flexible segment is reduced, resulting in sparse cross-linking points, and the tensile strength is reduced to about 30kPa, which is less than 50kPa in Example 5, and much less than 740kPa in Example 1, and the elongation at break is about 400%. When the molar ratio of lauryl methacrylate and 13-fluorooctyl methacrylate is 9:1 or 8:2, the proportion of flexible monomer (lauryl methacrylate) is too high, resulting in the weakening of the dynamic interaction between the molecular chains, the decrease in the cross-linking network density, and the insufficient rigid support, thereby reducing the adhesion of the elastomer material. Therefore, the protection scope proposed by the present invention has superiority. Due to the imbalance of the monomer ratio, the mechanical properties and adhesion of Comparative Examples 1 to 4 are significantly reduced, and the performance is not enough to meet the scene of high strength and high adhesion requirements. Therefore, the present invention finds the best balance between the ratio of flexible and rigid monomers to obtain an elastomer material with excellent mechanical properties and adhesion properties.
[0080] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A hydrophobic elastomer, characterized in that: The invention is prepared from lauryl methacrylate, tridecafluorooctyl methacrylate, a photoinitiator and a crosslinking agent.
2. The hydrophobic elastomer according to claim 1, characterized in that: The molar ratio of lauryl methacrylate to tridecafluorooctyl methacrylate is 3-7:7-3.
3. The hydrophobic elastomer according to claim 1, characterized in that: The photoinitiator is an oil-soluble photoinitiator; the content of the photoinitiator is 0.2% to 1.5% of the total amount of lauryl methacrylate and tridecafluorooctyl methacrylate.
4. The hydrophobic elastomer according to claim 1, characterized in that: The crosslinking agent is an acrylic ester crosslinking agent; the content of the crosslinking agent is 0.2% to 2% of the total amount of lauryl methacrylate and tridecafluorooctyl methacrylate.
5. The hydrophobic elastomer according to claim 1, characterized in that: The contact angle of water on the surface of the hydrophobic elastomer is greater than 100°.
6. The hydrophobic elastomer according to claim 1, characterized in that: The hydrophobic elastomer is cut and self-repaired for 12 to 24 hours, and the tensile strain of the self-repaired hydrophobic elastomer is 500% to 920%.
7. A method for preparing the hydrophobic elastomer according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: uniformly mixing lauryl methacrylate, tridecafluorooctyl methacrylate, a photoinitiator and a crosslinking agent; introducing an inert gas; and irradiating the mixture with ultraviolet light to obtain the hydrophobic elastomer.
8. The method for preparing a hydrophobic elastomer according to claim 7, characterized in that: Pass inert gas for 10 to 30 minutes; irradiate under ultraviolet light for 20 to 30 minutes.
9. Use of the hydrophobic elastomer according to any one of claims 1 to 6, characterized in that: The hydrophobic elastomer has self-adhesion force and can be applied to the adhesion of objects; the objects include metal, plastic, glass, and skin.
10. Use of the hydrophobic elastomer according to any one of claims 1 to 6, characterized in that: Used in the preparation of flexible electronics, medical patches, underwater sensors and waterproof materials.
Citation Information
Patent Citations
Underwater self-adhesion and self-repairing transparent ion conductive elastomer and synthesis method thereof
CN115651118A
Air suspension propping agent for fracturing slickwater as well as preparation method and application method of air suspension propping agent
CN106832145A
Short-fluorocarbon-chain acrylate polymer, preparation method thereof and application of short-fluorocarbon-chain acrylate polymer in release agent
CN113185636A
Solvent-free high-viscosity high-strength hydrophobic ion conductive elastomer and preparation method thereof
CN118388701A
High-damping heterogeneous hydrophobic ionic elastomer as well as preparation method and application thereof
CN118562047A